Acquired thrombotic thrombocytopenic purpura in a patient with plasmodium vivax malaria: A case report - Daren Esteban Araque Gualtero; Diego Augusto Moreno Diaz; Julie Melissa Mogollón; Andrés Felipe Gómez Rueda (Revista da Sociedade Brasileira de Medicina Tropical, 2024)
ABSTRACT Acquired thrombotic thrombocytopenic purpura (TTP) is a rare life-threatening disorder characterized by microangiopathic hemolytic anemia, severe thrombocytopenia, and organ damage. We present the case of a 71-year-old man initially diagnosed with malaria-like symptoms and displaying markers of microangiopathic hemolytic anemia, severe thrombocytopenia, renal injury, and neurological impairment. Despite antimalarial treatment, acquired TTP was suspected. Plasma exchange and immunosuppressive therapy led to clinical improvement, normalizing the platelet count and hemolytic profile. Diagnostic confirmation revealed significantly reduced ADAMTS13 levels. Following the proposed treatment, the patient's ADAMTS13 levels normalized. This case illustrates acquired TTP linked to uncomplicated Plasmodium vivax malaria.